2001
DOI: 10.1159/000048528
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Oxacillin-Hydrolyzing Beta-Lactamase in Borderline Methicillin-Resistant Clinical Isolates of <i>Staphylococcus aureus</i>

Abstract: Background: Mechanisms of borderline resistance of Staphylococcus aureus to penicillinase-resistant penicillins (PRPs) may include hyperproduction of classical penicillinase and/or production of β-lactamase hydrolyzing also PRPs. Methods: β-Lactamase activity of whole cells and purified enzymes was estimated spectrophotometrically and in isolated cytoplasmic membranes by bioassay with Bacillus subtilis as test strain. Results: Out of 53 clinical isolates of S. aureus, 18 showed oxacillin MIC values from 0.5 to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“… 51 This might be due to the fact that resistance to Methicillin in these isolates was not only due to the mec A gene since other modes of resistance to Methicillin such as the presence or over expression of ß-lactamase enzymes and chromosomal mutations have been documented. 52 , 53 The differences in the antimicrobial resistance rates to the various drugs observed might reflect a difference in regional antimicrobial usage and subsequent epidemiology due to inappropriate use of antibiotics in some regions. The choice of antibiotic for therapy of MRSA infections is usually complicated.…”
Section: Discussionmentioning
confidence: 99%
“… 51 This might be due to the fact that resistance to Methicillin in these isolates was not only due to the mec A gene since other modes of resistance to Methicillin such as the presence or over expression of ß-lactamase enzymes and chromosomal mutations have been documented. 52 , 53 The differences in the antimicrobial resistance rates to the various drugs observed might reflect a difference in regional antimicrobial usage and subsequent epidemiology due to inappropriate use of antibiotics in some regions. The choice of antibiotic for therapy of MRSA infections is usually complicated.…”
Section: Discussionmentioning
confidence: 99%
“…The so-called borderline-resistant strains that produce large amounts of β-lactamase and may hydrolyse methicillin, oxacillin and sometimes β-lactamase inhibitors as well appear as low-level methicillin resistant strains (McDougal and Thornsberry, 1986). However, it was shown that besides β-lactamase hyperproduction, a small increase in intrinsic resistance is required for the emergence of borderline resistance (Barg et al, 1991;Gál et al, 2001). Among clinical BORSA isolates methicillinase-producing strains were detected (Massida et al, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…4 S. aureus isolates with other types of resistance to β-lactams have been described and are known as borderline oxacillin-resistant S. aureus (BORSA) or intrinsically resistant S. aureus . 5,6 Resistance in some BORSA isolates is attributed to the presence or overexpression of β-lactamase enzymes, 6,7 while in intrinsically resistant and some BORSA isolates it is mediated by chromosomal mutations. 5,8,9 Furthermore, in vitro studies generating β-lactam-resistant isolates under the selection of β-lactam antibiotics have also identified a number of other genes able to mediate intrinsic β-lactam resistance.…”
Section: Introductionmentioning
confidence: 99%